Advancement of door-to-needle times in acute stroke treatment after repetitive process analysis: never give up!. (September 2022) - Ernst, Johanna; Storch, Kai F.; Tran, Anh Thu; Gabriel, Maria M.; Leotescu, Andrei; Boeck, Anna-Lena; Huber, Meret K.; Abu-Fares, Omar; Bronzlik, Paul; Götz, Friedrich; Worthmann, Hans; Schuppner, Ramona; et al.
Background: In acute ischemic stroke, timely treatment is of utmost relevance. Identification of delaying factors and knowledge about challenges concerning hospital structures are crucial for continuous improvement of process times in stroke care. Objective: In this study, we report on our experience in optimizing the door-to-needle time (DNT) at our tertiary care center by continuous quality improvement. Methods: Five hundred forty patients with acute ischemic stroke receiving intravenous thrombolysis (IVT) at Hannover Medical School were consecutively analyzed in two phases. In study phase I, including 292 patients, process times and delaying factors were collected prospectively from May 2015 until September 2017. In study phase II, process times of 248 patients were obtained from January 2019 until February 2021. In each study phase, a new clinical standard operation procedure (SOP) was implemented, considering previously identified delaying factors. Pre- and post-SOP treatment times and delaying factors were analyzed to evaluate the new protocols. Results: In study phase I, SOP I reduced the median DNT by 15 min. The probability to receive treatment within 30 min after admission increased by factor 5.35 [95% confidence interval (CI): 2.46–11.66]. Further development of the SOP with implementation of a mobile thrombolysis kit led to a further decrease of DNT by 5 min in median in study phase II. The median DNT was 29 (25th–75th percentiles: 18–44) min, and the probability to undergo IVT within 15 min after admission increased by factor 4.2 (95% CI: 1.63–10.83) compared with study phase I. Conclusion: Continuous process analysis and subsequent development of targeted workflow adjustments led to a substantial improvement of DNT. These results illustrate that with appropriate vigilance, there is constantly an opportunity for improvement in stroke care.